Najib Kailani and the Construction of Eastern Identity: Representation of Society in Egyptian Arabic Literature - Rizky Alifiandi; Muhamad Adji; Tisna Prabasmoro (Eduvest - Journal of Universal Studies, 2025)
The profound impact of colonialism and Westernization has often been overlooked in studies examining the portrayal of Eastern identity in Arabic literature. This research examines two novels by Najib Kailani, Al-Yawmu Al-Maw'ūd (1960) and Mawakib Al-Ahrār (1985), which reconstruct two distinct colonial periods using Egypt as a narrative setting. The primary aim of this study is to identify and analyze the narrative techniques employed by Kailani to depict Eastern societies and his endeavor to construct and preserve an Eastern identity. Using a qualitative method grounded in the theoretical approaches of narratology, representation, identity, and Occidentalism, this research addresses an urgent and novel gap by elucidating how Eastern identity is constructed in Arabic literature as a response to colonialism and the hegemony of Western discourse. In doing so, it adopts an epistemological approach rooted in Eastern perspectives. The study argues that the novels reaffirm the role of Arabic literature as a medium of resistance and a means of strengthening the collective identity of Eastern societies in the face of colonial and cultural hegemony.